2016
DOI: 10.1371/journal.pone.0164388
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Parkinson Disease and Brain Tumor: A Meta-Analysis

Abstract: ObjectiveEpidemiological studies have investigated the association between Parkinson disease (PD) occurrence and the risk of brain tumors, while the results remain controversial. We performed a meta-analysis to clarify the exact relationship between PD and brain tumors.MethodsA systematic literature search was conducted using PubMed, Embase, ScienceDirect and CBM (China Biology Medicine Disc) before February 2016. Eligible studies were those that reported risk estimates of brain tumors among patients with PD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…While most of the studies suggest an overall negative association between PD and cancer, some studies have indicated the opposite. For example, several studies have reported that PD patients are at higher risk of developing brain tumors (Lin et al, 2015 ; Tang et al, 2016 ; Ye et al, 2016 ) and breast cancer in women (Olsen et al, 2005 ; Rugbjerg et al, 2012 ). Additionally, PD patients harboring a G2019S LRRK2 mutation have been shown to have higher cancer rates than non-mutation carriers, especially for hormonal-related cancers and breast cancer in women (Agalliu et al, 2015 ).…”
Section: Cancer and Parkinson’s Diseasementioning
confidence: 99%
“…While most of the studies suggest an overall negative association between PD and cancer, some studies have indicated the opposite. For example, several studies have reported that PD patients are at higher risk of developing brain tumors (Lin et al, 2015 ; Tang et al, 2016 ; Ye et al, 2016 ) and breast cancer in women (Olsen et al, 2005 ; Rugbjerg et al, 2012 ). Additionally, PD patients harboring a G2019S LRRK2 mutation have been shown to have higher cancer rates than non-mutation carriers, especially for hormonal-related cancers and breast cancer in women (Agalliu et al, 2015 ).…”
Section: Cancer and Parkinson’s Diseasementioning
confidence: 99%
“…There are several situations when patients with actively implanted DBS devices need MRI. A majority require it as a part of diagnostic workup for various conditions such as acute ischemic stroke or postoperative hemorrhage [25,41,42]. The second scenario involves postoperative evaluation to document electrode location.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mutations or deletions in the human E3-ubiquitin ligase-coding gene PARK2 that lead to increased levels of cyclin E and re-entry of the cell cycle, are associated with both, several malignancies and early onset Parkinson’s disease ( Morris et al 2010 ). Indeed, recent epidemiological studies have identified positive associations between Parkinson’s disease and an increased risk of malignant brain tumors ( Lin et al 2015 ; Ye et al 2016 ). brat chs flies may serve in the future as an excellent model to investigate the mechanisms that underlie both conditions and may open novel avenues for therapeutic strategies and more targeted treatments for both cancer and neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 99%